1998
DOI: 10.1182/blood.v92.3.877.415k11_877_887
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HOX11 Leads to the Immortalization of Embryonic Precursors With Both Primitive and Definitive Hematopoietic Potential

Abstract: Primitive and definitive erythropoiesis represent distinct hematopoietic programs that differ with respect to stage of development, transcriptional control, and growth regulation. Although these differences have been recognized for some time, the relationship of the two erythroid lineages to each other is not well established. We have used a model system based on the hematopoietic development of embryonic stem (ES) cells in culture to investigate the origins of the earliest hematopoietic populations. Using ES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 50 publications
5
29
0
Order By: Relevance
“…Previous literature has indicated that TLX1 expression can induce proliferative/anti-differentiative effects in diverse haemopoietic cell types (Hawley et al, 1994;Hawley et al, 1997;Kawabe et al, 1997;Hough et al, 1998;Keller et al, 1998;Greene et al, 2002;Yu et al, 2002;Owens et al, 2006). Here, we have confirmed and extended these findings by showing that TLX1 can act as a broad and powerful inhibitor of haemopoiesis while promoting a non-haemopoietic phenotype.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous literature has indicated that TLX1 expression can induce proliferative/anti-differentiative effects in diverse haemopoietic cell types (Hawley et al, 1994;Hawley et al, 1997;Kawabe et al, 1997;Hough et al, 1998;Keller et al, 1998;Greene et al, 2002;Yu et al, 2002;Owens et al, 2006). Here, we have confirmed and extended these findings by showing that TLX1 can act as a broad and powerful inhibitor of haemopoiesis while promoting a non-haemopoietic phenotype.…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with this finding, a similar study has also recently found that enforced expression of TLX1 leads to an early arrest of thymocyte differentiation (Owens et al, 2006). Despite specifically being a T-cell oncogene in humans, however, previous studies have shown that TLX1 can act more broadly to block cell differentiation within various haemopoietic lineages (Hawley et al, 1994;Keller et al, 1998;Greene et al, 2002;Yu et al, 2002). In order to gain further insight into the nature of this widespread interference with haemopoietic cell differentiation, we examined the effects of constitutive TLX1 expression on adult murine BM cells, both in vitro and in vivo, following retroviral transduction.…”
Section: Retroviral Expression Of Tlx1/hox11 In Murine Haemopoietic Csupporting
confidence: 60%
“…In conclusion, these findings establish the feasibility of bypassing senescence in human hematopoietic progenitors through genetic engineering, providing proof of principle for approaches that might eventually allow establishment of permanent human hematopoietic stem cell lines. Accordingly, our future efforts will focus on extending these results by using reversible gene delivery systems [50] and a variety of growth regulatory genes (e.g., TLX1/ HOX11) [22,51] toward the conditional immortalization of other human hematopoietic stem/progenitor cell subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical to include IL-3 in the medium after the coculture and all subsequent steps. However, the IL-3-containing medium can be supplemented with other cytokines/growth factors, e.g., SCF, Epo (Keller et al, 1998;Yu et al, 2002;Riz et al, 2007). While selection for retrovirally transduced cells with Geneticin or hygromycin B is recommended, it is not strictly required since TLX1-expressing cells will exhibit a growth advantage over nontransduced cells during in vitro passaging (Yu et al, 2002;Su et al, 2006) and nontransduced cells should eventually disappear from the cultures due to senescence.…”
Section: Prepare Hematopoietic Progenitor Cellsmentioning
confidence: 99%
“…Therefore, it is critical to include IL-3 in the medium after the coculture and in all subsequent steps. However, the IL-3-containing medium can be supplemented with other cytokines/growth factors, e.g., SCF, Epo (Keller et al, 1998;Yu et al, 2002;Riz et al, 2007). 23. Select for TLX1-expressing cells (step 24) as early as 48 to 72 hr following the coculture, or passage cells in immortalized cell medium with the selective agent at 1:10 to 1:20 every 3 to 4 days, with gentle pipetting up and down to disrupt cell clusters.…”
mentioning
confidence: 99%